PREPARATION OF FUTURE PRIMARY TEACHERS CLASSES FOR ASSEMBLY AND STRUCTURING EDUCATIONAL AND COGNITIVE TASKS IN READING LESSONS (Pedagogy of Higher and Secondary Education, 2022)
The problems of professional preparation of future teachers of initial classes are explored in the article. The question of drafting and application o f educational-cognitive tasks is lighted to work of students with the texts of textbook on the lessons of reading.